Feminist engagement in international criminal law: a historiographical analysis - El Saeed, Sarah (AUC Knowledge Fountain, 2014)
This text aims at providing a broad analytical historiography of feminist engagement in international criminal law from the early 20th century until the formation of the modern international legal field with the drafting of the Rome Statute and establishment of the International Criminal Court. It traces the evolvement and coming of age of both the global feminist movement and the international criminal legal project, and the manner in which they came to intersect. The text outlines the modes and methods of feminist engagement in the field, provides a proposed model of the involvement of feminist typologies in international criminal law, and specifically examines the manner in which liberal feminism, versus others, has interacted with various areas of international law.